2021
DOI: 10.3389/fpubh.2021.795284
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Medicine: A Multinational Multi-Center Survey on the Medical and Dental Students' Perception

Abstract: Background: The emerging field of artificial intelligence (AI) will probably affect the practice for the next generation of doctors. However, the students' views on AI have not been largely investigated.Methods: An anonymous electronic survey on AI was designed for medical and dental students to explore: (1) sources of information about AI, (2) AI applications and concerns, (3) AI status as a topic in medicine, and (4) students' feelings and attitudes. The questionnaire was advertised on social media platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 35 publications
(41 reference statements)
8
73
4
Order By: Relevance
“…AI has experienced great advances in recent years, causing a great impact on science, economics, and education [ 36 ]. In reference to the field of education, in some previous studies with students of health branches [ 40 , 41 ], they valued very positively, as in the present study, the interaction with artificial intelligences. Moreover, as in this study, they affirmed the need to implement this technology in the curricula.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…AI has experienced great advances in recent years, causing a great impact on science, economics, and education [ 36 ]. In reference to the field of education, in some previous studies with students of health branches [ 40 , 41 ], they valued very positively, as in the present study, the interaction with artificial intelligences. Moreover, as in this study, they affirmed the need to implement this technology in the curricula.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, students who teach with patients highly value observational or vicarious learning [ 45 ] together with their fellow trainees. All of these reasons may explain the lack of updating in these developments in dental school [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical students also felt that they mainly heard about AI from media and colleagues, but received minimal training from their schools ( 18 , 30 ). Accordingly, 15 studies suggested an urgent need to integrate AI into residency programs or school curricula ( 17 19 , 21 , 29 – 33 , 38 , 41 , 45 , 49 51 ). Our questionnaire appears to confirm this situation with few respondents having good knowledge of AI (13% agreement).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five included studies mentioned the views of physicians and medical students on clinical AI, and more than 60% of the respondents in 38 (84.44%) studies had an optimistic outlook regarding it ( 11 , 12 , 17 20 , 22 26 , 29 , 30 , 32 , 33 , 35 , 36 , 38 41 , 45 61 ). For example, 75% of 487 pathologists from 59 countries were enthusiastic about the progress of AI ( 11 ); 77% of 1271 dermatologists from 92 countries agreed that AI would improve dermatologic practice ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation